2009
DOI: 10.3354/ab00185
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of cold-water coral-derived organic matter: potential implication for organic C cycling in the water column above Tisler Reef

Abstract: Cold-water corals release organic matter, in particular mucus, but its role in the ecological functioning of reef ecosystems is still poorly understood. The present study investigates the planktonic microbial degradation of mucus released by Lophelia pertusa colonies from Tisler Reef, Skagerrak. Results are compared to the degradation of dissolved and particulate organic substrates, including the carbohydrates glucose and starch, as well as gum xanthan and the cyanobacterium Spirulina spp. as the model organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…The assimilation of external DOM and the re-assimilation of DOM from coral mucus release, responsible for high labile DOM concentrations above CWC reefs (van Duyl et al, 2008;Wild et al, 2009) might help the coral to withstand several months without POM supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assimilation of external DOM and the re-assimilation of DOM from coral mucus release, responsible for high labile DOM concentrations above CWC reefs (van Duyl et al, 2008;Wild et al, 2009) might help the coral to withstand several months without POM supply.…”
Section: Discussionmentioning
confidence: 99%
“…This might be especially relevant since bacteria occur in high abundance around cold-water coral reefs and food uptake in L. pertusa is positively correlated with prey abundance (Purser et al, 2010). Additionally, bacteria are constantly available to the coral since they are fertilized by the coral itself via mucus production (Wild et al, 2009;Maier et al, 2011), while POM availability can vary spatially and temporally (Duineveld et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The alkalinity anomaly technique used in this study has the advantage that it is sensitive enough to use for short-term incubations and that corals can be kept alive. However, it has been shown that L. pertusa and M. oculata excrete inorganic nutrients and that bacterial growth is stimulated during incubations owing to the release of organic matter [38,41,42]. This may also alter the T A during incubation.…”
Section: Discussion (A) Methodological Constraints (I) On-board Expermentioning
confidence: 99%
“…live stands, dead coral and rubble) would likely alter oxygen uptake rates (e.g. Wild et al 2009, Wagner et al 2011), but the approach here was to assess a bulk respiration rate for the CWC ecosystem and provide a first order estimate. There was evidence for significant seasonal variability in oxygen uptake rates, as might be expected.…”
Section: Discussionmentioning
confidence: 99%